Swimming and acoustic calling behavior attributed to Bryde’s whales in the central North Pacific - Helble, Tyler A.; Alongi, Gabriela C.; Guazzo, Regina A.; Allhusen, Dylan R.; Martin, Cameron R.; Martin, Stephen W.; Durbach, Ian N.; Henderson, E. Elizabeth (Frontiers in Marine Science, 2024)
A unique acoustic call type was identified and attributed to Bryde’s whales in the central North Pacific in 2015, but little is known about the distribution, calling behavior, or swimming behavior of Bryde’s whales in the region. Acoustic detections attributed to Bryde’s whales were used to localize and track individual whales on the U.S. Pacific Missile Range Facility (PMRF) in Kaua‘i, Hawai‘i. This study included 150 acoustically derived tracks from recordings spanning the years 2011–2022 with recording effort in nearly every month. Bryde’s whale movement was examined relative to calendar year, day of year, hour of day, wind speed, and acoustic calling rate. Hidden Markov models were used to identify two kinematic states (slower, less directional movement and faster, more directional movement). The findings indicate that Bryde’s whales were more likely to travel in a faster and more directional state during the daytime than at night and between May and August when compared to other times of year. The along-track acoustic cue rate was examined for 118 tracks, and the findings indicate a possible lengthening of the median inter-call interval over the duration of the study period. These results are an important first step in understanding more about behavior in Bryde’s whales, a relatively under-studied species.